Pola Pergerakan Perilaku Agonistik Lobster Air Tawar Cherax quadricarinatus (Von Martens, 1868) - Tarjono Tarjono; Mufti P. Patria (Universitas Atma Jaya Yogyakarta, 2010)
This research on movement patterns of agonistic behavior in crayfish Cherax quadricarinatus was conducted at laboratory and used an aquarium size 25 cm x 10 cm x 15 cm. The patterns of agonistic behavior were recorded by using a CCD and digital camera. The recorded data were analyzed using The Adobe Premier computer program and using Jaccard similarity to solve the reciprocal movement patterns. Clustering based on the UPGMA (Unweighted Pair Group Method Average) indicated that the dissimilarity value was about 0,98 and the moving pattern of the agonistic behaviors were grouped into five groups, namely: 1) threatening; 2) arranging the strategy; 3) testing the enemies capability; 4) fighting; 5) avoiding and defending.